1992
DOI: 10.1288/00005537-199212000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The management of subglottic stenosis in patients with wegener's granulomatosis

Abstract: Wegener's granulomatosis (WG) is a multisystem inflammatory disease characterized by vasculitis, granuloma formation, and necrosis. Among 158 patients treated at the National Institutes of Health during the past 24 years, 145 (92%) had an otolaryngologic manifestation of their disease and 25 (16%) had subglottic stenosis (SGS). SGS varied from asymptomatic to life-threatening. Sixteen (80%) of 20 patients with fixed SGS required surgical intervention, including manual dilations, carbon-dioxide laser resections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
2
31

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 11 publications
6
97
2
31
Order By: Relevance
“…It has been recognized that in distinction from adults, childhood GPA patients develop nasal deformity and SGS more frequently (4 -6,8,10,11). Large adult GPA studies have found a 24% prevalence of nasal deformity and a 10% prevalence of SGS (4,11). In concurrence with previous pediatric studies, 29% of our patients developed nasal deformity (aforementioned range 20 -48%) and 43% developed SGS (historical range 41-48%) (4 -6).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been recognized that in distinction from adults, childhood GPA patients develop nasal deformity and SGS more frequently (4 -6,8,10,11). Large adult GPA studies have found a 24% prevalence of nasal deformity and a 10% prevalence of SGS (4,11). In concurrence with previous pediatric studies, 29% of our patients developed nasal deformity (aforementioned range 20 -48%) and 43% developed SGS (historical range 41-48%) (4 -6).…”
Section: Discussionsupporting
confidence: 91%
“…Details regarding airway manifestations in childhood GPA have been limited in prior studies (4 -9). Differences between adult and childhood GPA include statistically higher prevalences of nasal deformity and subglottic stenosis (SGS) (4,6,8,10,11). Additionally, it has been proposed that GPA may encompass 2 diseases: limited and generalized (12).…”
Section: Introductionmentioning
confidence: 99%
“…1 Ainda, 85% das manifestações clínicas iniciais ocorrem em maiores de 20 anos de idade, sendo estas raras na população pediátrica, cuja incidência varia de 6 a 14%. 2,3 As formas clínicas podem variar de localizadas ao acometimento multissistêmico. Critérios para definição de doença incluem: comprometimento nasal ou oral; alterações radiográficas características; microhematúria ou cilindros hemáticos em exames de urina e alteração histológica compatível com inflamação granulomatosa de parede arterial ou perivascular.…”
Section: Introductionunclassified
“…5,6 Os protocolos de tratamento medicamentoso incluem a utilização de glicocorticóides e/ou imunossupressores, dentre eles a ciclofosfamida, permitindo índices satisfatórios de remissão da doença. 1,3,5,7,8 As manifestações otorrinolaringológicas têm elevada prevalência, tanto em apresentações clínicas iniciais, como fazendo parte do curso habitual da doença. Sintomas nasofaríngeos e laríngeos podem estar presentes em até 73% dos casos.…”
Section: Introductionunclassified
See 1 more Smart Citation